Astrotourism and ecological awareness: Investigating emotional encounters with the night sky - Adhika Graha Irianto Putra; Bambang Hermanto; Yunus Winoto; Awaludin Nugraha; Hanhan Hanafiah Solihin (Journal of Environment and Sustainability Education, 2025)
Light pollution has become an urgent environmental concern that reduces access to naturally dark skies and contributes to ecological amnesia, the fading of direct connections with the natural world. This study examines how first-time encounters with an unpolluted night sky through astrotourism evoke emotional responses that foster ecological awareness. The research used an interpretative phenomenological approach with ten novice participants who shared their initial experiences in dark-sky environments. The findings reveal affective responses of awe, wonder, existential reflection, and intergenerational concern. These responses transformed passive observation into embodied engagement with the cosmos. Within the framework of emotional geography, the night sky is conceptualized as an affective landscape that restores ecological intimacy and supports environmental reflection. The study positions astrotourism as more than recreation and highlights its potential as an affective pedagogy in environmental education and as a pathway for sustainable tourism. The novelty of this study lies in framing astrotourism as an affective bridge between emotional geography and environmental education.